2015
DOI: 10.1080/1059924x.2015.1009668
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Agricultural and Logging Injury Incidence in Maine Using Electronic Administrative Data Sets

Abstract: Agriculture and forestry rank among industries with the highest rates of occupational fatality and injury. Establishing a nonfatal injury surveillance system is a top priority in the National Occupational Research Agenda. Recently, new sources of data such as Pre-Hospital Care Reports (PCRs) and hospitalization data have transitioned to electronic databases. Using narrative free text and location codes from Maine PCRs, along with International Classification of Diseases (ICD)-9 External Cause of Injury Codes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…13 The Maine agricultural and logging data were derived from administrative data for ambulance runs and hospitalizations and did not distinguish work and non-work related injuries (2008). 14 The Minnesota data were derived from an administrative hospital discharge database and did not distinguish work and non-work related injuries (2000–2011). 15 We found that the use of administrative data without the review of medical records would lead to a 65% over count.…”
Section: Discussionmentioning
confidence: 99%
“…13 The Maine agricultural and logging data were derived from administrative data for ambulance runs and hospitalizations and did not distinguish work and non-work related injuries (2008). 14 The Minnesota data were derived from an administrative hospital discharge database and did not distinguish work and non-work related injuries (2000–2011). 15 We found that the use of administrative data without the review of medical records would lead to a 65% over count.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were also made to identify recreational activities that took place in the farm location (e.g., riding horses or ATVs). Medically-attended farm-related injuries were ascertained based on adaptations of injury surveillance models outlined by Landsteiner et al ( 23 ) and Scott et al ( 24 , 25 ). Injury details were extracted from medical diagnoses observed during emergency, inpatient, urgent care, or outpatient encounters in the MCHS electronic data repository.…”
Section: Methodsmentioning
confidence: 99%
“…National surveillance systems that apply uniform definitions and coding schemes provide value to stakeholders and facilitate collaborations between researchers nationally and internationally. 12,[14][15][16][17] Yet, gaps remain in national statistics, and support is needed to supplement current national surveillance to be more inclusive and comprehensive, recognizing the whole spectrum of agriculturerelated injury and fatality cases.…”
Section: Implications and Recommendationsmentioning
confidence: 99%